Risks and vulnerabilities of injectable administration in health promotion settings with the impact of lack of biosafety - Santos, Natália Figueiredo dos (Seven Editora, 2023)
Biosafety is a set of measures aimed at preventing, minimizing or eliminating risks inherent to activities in occupational environments. Several problems have been reported regarding the lack of biosafety, especially in health care facilities that have sectors associated with the manipulation of injectables and other invasive procedures. Therefore, describing the performance of the pharmaceutical professional in relation to biosafety management directs a technical qualification seeking to identify, minimize and even eradicate risks and vulnerabilities associated with these invasive practices with the possible exposure of biological fluids to which they are exposed. Thus, the objectives of this study were to analyze  and discuss the risks and vulnerabilities of injectable administration in health promotion environments, indicating the impact of the lack of biosafety. To this end, we conducted a small literature review, in addition to a field research among pharmacists in the Lakes Region, State of Rio de Janeiro, where an online questionnaire with  19 closed questions on the theme already explained above was applied. Our results found a wide variety of studies related to the theme, corresponding to the data found in the participation of 20 pharmacists who were technicians in charge, working in pharmacies with injectables or who had already worked in this practice. The results were impactful because they confirmed the fragility of many professionals who work with injectable injections. Lack of knowledge in current legislation, other disabled professionals performing these activities without proper preparation, among other difficulties. In view  of the results obtained in the research, it is concluded that there is a need to broaden the discussion on occupational risks, work accidents and vulnerability in the practices of health professionals, with the objective of developing health policies for pharmaceutical professionals. DOI:https://doi.org/10.56238/sevened2023.004-044